Is shared decision-making a determinant of polypharmacy in older patients with chronic disease? A cross-sectional study in Hubei Province, China - Qiao Zong; Zhanchun Feng; Jia Wang; Zehao Zheng; Chaoyi Chen; Da Feng (BMC Geriatrics, 2023)
Abstract Background Shared decision-making(SDM) is recognized as an important means of managing polypharmacy among older people with chronic diseases. However, no studies have quantitatively measured the effect of SDM on polypharmacy. The objective of this study was to compare the impact of SDM and other factors on polypharmacy in inpatients and community patients. Additionally, the study aimed to compare the impact of different decision types on polypharmacy in community patients. Methods This is a population-based multicenter retrospective study conducted in Hubei Province, China. A cluster sampling approach was used to recruit 536 chronic disease inpatients from March to April 2019, and 849 community patients were recruited from April to June 2021. Propensity score weighting was used to control the confounding variables and determine the net effect of SDM on polypharmacy. Results Among the 536 hospitalized patients, the prevalence of polypharmacy was 56.3%. A high level of SDM was significantly associated with a lower risk of polypharmacy. Patients with chronic illnesses aged 76 years and older and with an annual family income of 24,001–36,000 yuan were associated with a lower likelihood of polypharmacy (p < 0.05). Multimorbidity was often accompanied by the occurrence of multiple medication use. Among 849 community patients, the prevalence of polypharmacy was 21.8%. Among types of decision-making, informed and paternalistic decision-making showed a higher likelihood of polypharmacy compared with shared decision-making (P < 0.05). Male, older patients over 76 years of age, urban residents, annual household income of 12,001–24,000 yuan, and multimorbidity were associated with higher likelihood of polypharmacy (P < 0.05). Patients with an annual household income of 24,001–36,000 yuan, 36,001 yuan or more, and good medication compliance showed a lower likelihood of polypharmacy (P < 0.05). Conclusions The prevalence of polypharmacy is high among China's older population with chronic disease who should be paid more atthention by the healthcare providers. Additionaly, encouraging the patients' attendance in SDM, reducing paternalistic and informed decision-making during prescribing, improving patient medication compliance, and increasing the promotion and guidance of rational medication use for patients are essential to reduce polypharmacy in Chinese chronic disease patients.